Persuasive business proposals : writing to win more customers, clients, and contracts - Sant, Tom (AMACOM, American Management Association, 2012)
Writing a winning proposal has always been an important part of sales. In recent years it has become vital. But many companies are still cranking out confusing, unpersuasive proposals and RFPs-few of which result in new clients or contracts. Now everyone can dramatically boost their success rate with the third edition of Persuasive Business Proposals. This classic guide explains how to craft compelling messages and powerful proposals that attract prospects' attention and speak to their needs. The new edition includes more valuable information than ever before, including: * Essential questions.